Functional nanocomposites based on the infusion or in situ generation of nanoparticles into amphiphilic epoxy gels - Ledo Suárez, Ana (2010)
The production of nanocomposites with functional properties via the infusion of preformed nanoparticles (NPs) or their in situ generation inside an amphiphilic epoxy gel is reported. The gel was synthesized by the reaction of a diepoxy monomer based on diglycidyl ether of bisphenol A with an n-alkylamine, followed by annealing the resulting linear polymers above their glass transition temperatures to produce physical gelation through tail-to-tail association of pendant alkyl chains. Some of the advantages of these polymer gels are: (a) they have a low crosslink density and can therefore be significantly swollen by several organic solvents, (b) the presence of pendant alkyl chains provides a convenient chemical environment for the stabilization of NPs coated with alkyl chains, (c) the presence of secondary hydroxyls and tertiary amine groups in the polar backbone of polymer chains can be used to coordinate and reduce different precursors of NPs. Preformed NPs could be successfully infused into the gels keeping their optical properties (e.g., CdSe quantum dots) or magnetic behavior (e.g., γ-Fe2O3@oleic acid NPs) in the resulting nanocomposite. In situ generation of Au and Ag NPs (average size close to 10 nm) inside the amphiphilic gels was produced by infusing HAuCl4 or AgNO3 followed by reduction to the corresponding metals with secondary alcohols present in the polymer backbone, at 100 °C. Amphiphilic gels were employed as hosts for the in situ precipitation of gold(i)-dodecanethiolate leading to films exhibiting a red emission (638 nm) when excited with UV light (300 nm).